12.2: Narrow Angle Scattering Measurement of PDLC/PNLC Smart Window. (24th February 2021) - Tang, Shu Tuen; Chiu, Hon Wah; Tseng, Man Chun; Kwok, Hoi Sing
Abstract : PDLC based smart window is currently the choice of switchable privacy window widely used in hotels and conference rooms. The ability of image hiding behind the window is now represented by the percentage haziness according to ASTM D1003 (or equivalent GB2410‐2008). The ASTM D1003 is originally designed for measuring wide angle light scattering with haze value less than 30%. This is not quite suitable for high haze level PDLC measurement. In this article, we introduce a narrow angle scattering (NAS) method that can better correlate the image hiding level and the measurement readings. An image hiding factor (IHF) is also introduced by making use of the narrow angle scattering measurement results.